Gender differences in injuries attributed to workplace violence in Ontario 2002–2015 - Chen, Cynthia (Occup Environ Med, 2019)
OBJECTIVES: The aim of the study is to compare trends in the incidence of injury resulting from workplace violence for men and women at the population level over the period 2002–2015 among working-age adults in Ontario, Canada. METHODS: Administrative records of injury resulting from workplace violence were obtained from two population-based data sources in Ontario: 21 228 lost-time workers’ compensation claims (2002–2015) and 13 245 records of non-scheduled emergency department visits (2004–2014), where the main problem was attributed to a workplace violence event. Denominator counts were estimated from labour force surveys conducted by Statistics Canada, stratified by age and sex. Age-standardised rates were calculated using the direct method. RESULTS: Over the observation period, workplace violence incidence rates were in the range of 0.2–0.5 per 1000 full-time equivalent workers. Incidence rates of injury due to workplace violence among women increased over the observation period, with an average annual per cent change (APC) of 2.8% (95% CI 1.7% to 3.9%) in compensation claims and 2.7% (95% CI 1.0% to 4.4%) in emergency department visits. In contrast, there was no change in workplace violence injury rates among men in compensation claims (APC: −0.2% (95% CI −1.2% to 0.9%)) or in emergency department visits (APC: −0.5% (95% CI −1.6% to 0.6%)). A pronounced increase in workplace violence injury rates was observed in the education sector with an APC=7.0% (95% CI 5.6% to 8.5%) for women and an APC=4.1% (95% CI 0.9% to 7.4%) for men. CONCLUSIONS: Differences in the risk of injury resulting from workplace violence for women relative to men in Ontario between 2002 and 2015 were verified by two data sources. The relative risk of violence for men and women also differed across industries.